2021
DOI: 10.3389/fmolb.2021.666705
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of the Network Reconstruction Approaches on Various Interactomes

Abstract: Beyond the list of molecules, there is a necessity to collectively consider multiple sets of omic data and to reconstruct the connections between the molecules. Especially, pathway reconstruction is crucial to understanding disease biology because abnormal cellular signaling may be pathological. The main challenge is how to integrate the data together in an accurate way. In this study, we aim to comparatively analyze the performance of a set of network reconstruction algorithms on multiple reference interactom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 110 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…Graph-based filters aim to trim networks while keeping important nodes such as seeds, hubs or bottlenecks. A new graph-based filter in version 2.0 is the Prize-collecting Steiner Forest (PCSF) algorithm ( 34 ), which has been shown to give balanced performance in a recent benchmark study ( 35 ). To further assist users in network refinement, we have added a topology dialog to show graphical summaries of node degree and betweenness distributions for each subnetwork.…”
Section: Program Description and Methodsmentioning
confidence: 99%
“…Graph-based filters aim to trim networks while keeping important nodes such as seeds, hubs or bottlenecks. A new graph-based filter in version 2.0 is the Prize-collecting Steiner Forest (PCSF) algorithm ( 34 ), which has been shown to give balanced performance in a recent benchmark study ( 35 ). To further assist users in network refinement, we have added a topology dialog to show graphical summaries of node degree and betweenness distributions for each subnetwork.…”
Section: Program Description and Methodsmentioning
confidence: 99%
“…Recent studies have shown that when integrating different types of biological data (such as genomic, proteomic, and transcriptomic data) to reconstruct signaling networks, using hybrid approaches can be more effective than relying on a single method alone 16 . The accuracy of reconstructed networks is also highly dependent on the quality of the reference interactome 42,43 . However, there are tradeoffs involved in increasing the number of interactions in the reference interactome.…”
Section: Overview Of Pyparagon As a Hybrid Network Inference Frameworkmentioning
confidence: 99%
“…Each available interactome has a specific evaluation and scoring scheme to integrate PPIs from different resources 42 . In this study, we used ConsensusPathDB, HIPPIE v2.2, and HIPPIE v2.3 which have different topological features (Supplementary Table 1).…”
Section: Network Trimming Via Graphlets Improves the Network Inferencementioning
confidence: 99%
See 1 more Smart Citation
“…[ 122 ]. In addition, the structural features of inferred networks, such as PageRank, heat diffusion, the shortest path, etc., can be used to compare GRNs inferred from different methods [ 123 ], whereas other metrics can be used to define the method performance, such as stability (across simulations, artificially removing measurements), identification of network motifs, and computational time and memory usage [ 98 ].…”
Section: Grn Validationmentioning
confidence: 99%